2021
DOI: 10.3389/fsufs.2021.645197
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Agricultural Byproducts and Cover Crops as Anaerobic Soil Disinfestation Carbon Sources for Managing a Soilborne Disease Complex in High Tunnel Tomatoes

Abstract: Anaerobic soil disinfestation (ASD) is a viable option for disease management in tomato production and reduces damage due to a soilborne disease complex consisting of Pyrenochaeta lycopersici, Colletotrichum coccodes, Verticillium dahliae, and Meloidogyne spp. There are plentiful options for ASD carbon sources using byproducts of Midwestern United States agriculture or cover crops, yet these carbon sources have not been evaluated for use in Midwestern settings. Low (10.1 Mg/ha) and high (20.2 Mg/ha) rates of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Therefore, the development of anaerobic conditions is beneficial to generate a fumigant effect against pathogens and weeds [58][59][60][61][62]. Previous research applied corn gluten meal for ASD, significantly reducing the soilborne disease intensity on tomatoes grown in treated plots [63]. However, the same authors reported a phytotoxic effect of corn gluten meal on the germination and growth of tomatoes [63].…”
Section: Impact Of Asd On Sclerotia Disease Reduction and Weed Contro...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the development of anaerobic conditions is beneficial to generate a fumigant effect against pathogens and weeds [58][59][60][61][62]. Previous research applied corn gluten meal for ASD, significantly reducing the soilborne disease intensity on tomatoes grown in treated plots [63]. However, the same authors reported a phytotoxic effect of corn gluten meal on the germination and growth of tomatoes [63].…”
Section: Impact Of Asd On Sclerotia Disease Reduction and Weed Contro...mentioning
confidence: 99%
“…Previous research applied corn gluten meal for ASD, significantly reducing the soilborne disease intensity on tomatoes grown in treated plots [63]. However, the same authors reported a phytotoxic effect of corn gluten meal on the germination and growth of tomatoes [63]. Corn gluten meal has been reported as an herbicide or a cause of phytotoxicity in plants [64].…”
Section: Impact Of Asd On Sclerotia Disease Reduction and Weed Contro...mentioning
confidence: 99%
“…Given these concerns, research is needed to develop sustainable alternatives. Anaerobic soil disinfestation (ASD) is garnering attention as a biological alternative to chemical soil fumigation (CSF) (Butler et al., 2012; Goud et al., 2004; Testen et al., 2021). Anaerobic soil disinfestation methods incorporate readily bioavailable carbon (C) sources (relative to microbes), such as rice bran, molasses (M), or crop residues into the soil, followed by irrigation of the soil to saturation and covering with totally impermeable film (TIF) for about 3 wk (Butler et al., 2014; Di Gioia et al., 2017; Paudel et al., 2020; Rosskopf et al., 2015,2020).…”
Section: Introductionmentioning
confidence: 99%
“…This last effect is mainly subject to the characteristics of the organic amendment. The concentration of C, N and their ratio in the final mixture seems to play an important role in treatment efficacy (Shrestha et al, 2021a;Testen et al, 2021). Besides, the type of C-source used might also condition the processes given during biodisinfestations.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in areas with limited solar radiation, like in our case, the selection of proper amendments is a challenge, since many organic by-products and vegetal materials can be used. Among them, some agro-industrial by-products have exhibited positive results (Lacasa et al, 2021;Testen et al, 2021) and might be a worthwhile alternative because it is costeffective and promotes circular economy.…”
Section: Introductionmentioning
confidence: 99%